LOCAL NORMS AND THE APPLICATION OF THE RIGHT TO SPORT BY MUNICIPALITIES FROM PIAUÍ - Edmilson Santos dos Santos; Luciano Juchem; Luiz Alcides Ramires Maduro (Journal of Physical Education)
ABSTRACT In recent years, important studies on the participation of municipalities in the expenses with the Sport and Leisure Function (SLF) have been published in Brazil, but little is known regarding variables affecting its results. For that matter, the present study aimed to verify the existence of a norm, in the scope of the organic law, capable of explaining the behavior of expenses with the SLF by municipalities from Piauí. The sample was composed of 44,64% (100) of municipalities in Piauí (224). The majority of the sample does not acknowledge the subject as an important one among other private competences (94%) and with full effectiveness (96%). Unlike the behavior of these two legislative classes, out of all municipalities that have not presented norms for the dealing with the subject, 1/3 has expended for 15 years. The organic law was not a good predictor of the behavior of expenses with the SLF by municipalities from Piauí.